Does long-term swimming participation have a deleterious effect on the adult female skeleton? - Greenway, K. G.; Walkley, J. W.; Rich, P. A. (European Journal of Applied Physiology, 2012)
Swimming is a popular activity for Australian women with proven cardiovascular benefits yet lacks the features thought necessary to stimulate positive adaptive changes in bone. Given that peak bone mass is attained close to the end of the second decade, we asked whether swimming was negatively associated with bone mineral density in premenopausal women beyond this age. Bone mass and retrospective physical activity data were gathered from 43 female swimmers and 44 controls (mean ages 40.4 and 43.8 years, respectively). Swimmers were recruited from the Australian Union of Senior Swimmers International while controls were healthy community dwellers with similar lean mass, fat mass, height, weight and body mass index. None of the participants had a history of medical complaints nor use of medications known to affect bone. Dual energy X-ray absorptiometry was used to determine areal bone mineral density at total body, lumbar spine, proximal femur, distal radius and tibia while self-administered questionnaires were used to approximate historical and recent physical activity and calcium intake. Swimmers had averaged over 2 hours of swimming per week for the past 5 years and 1.45 h/week over lifetime with no systematic swimming exposure for controls. Lifetime exposure to weight bearing and impact exercise were similar. There were no intergroup differences for bone mass at any site though controls had higher incidence of low bone mass/osteoporosis. No differences in bone mass were detected between swimmers in the upper and lower quartiles for swim participation for any period. Long-term swim participation did not compromise areal bone mineral density.